Streaming Apps and Music Consumption among the Nigerian Youth - AYOBOLU, Yetunde Oluwayemisi (Àgídìgbo: ABUAD Journal of the Humanities, 2025)
Music is an important part of the youth lifestyle and experience as it influences both their leisure and emotional well-being. Streaming applications such as Spotify, Apple Music and YouTube Music have revolutionised the way music is consumed offering unprecedented access to a vast array of genres and artists with the provision of personalised listening experiences through curated playlists and on demand access reshaping how the youth engage with music. This research examines the impact of these streaming applications on the youth’s music consumption with the theoretical framework built around the Uses and Gratification and the Technological Determinism theories. The descriptive survey design method was adopted with the use of questionnaire for data collection. One hundred and fifty respondents were randomly selected for the study with the data analysed using simple frequencies and percentages and presented in frequencies and percentages. Results indicate that streaming applications enhance music accessibility and variety allowing youths to explore new music effortlessly. However, challenges such as potential reduction in traditional music purchasing are also noted. The study recommends optimising streaming application usage by continually innovating interfaces and recommendation algorithms, thereby catering to diverse preferences and listening habits to foster greater engagement and loyalty among users.